The Role Of Il6 Gene C174g Polymorphism In The Progression Of Diabetic Foot Syndrome (Eurasian Journal of Learning and Academic Teaching, 2024)
The criteria for risk stratification of the formation of diabetic foot syndrome in patients with diabetes mellitus based on the carriage of the interleukin 6 gene were studied. The clinical group included 96 patients aged 40 to 75 years with diabetes mellitus complicated by diabetic foot syndrome. The control group consisted of 83 healthy individuals. The results obtained by the authors demonstrate that the presence of the C/G genotype of the C174G polymorphism of the IL6 gene has a clear correlation with predisposition to the development of diabetic foot syndrome. In order to effectively prevent the development of diabetic foot syndrome, it is advisable to recommend genotyping of the C174G polymorphism in the IL6 gene